2021
DOI: 10.3390/educsci11050215
|View full text |Cite
|
Sign up to set email alerts
|

The School and the Teacher Autonomy in the Implementing Process of Entrepreneurship Education Curricula

Abstract: The purpose of this study was to examine the utilization of the opportunities offered by teacher and school autonomy in entrepreneurship education with companies involved. The research question was: How do schools and teachers use their autonomy in the implementation of entrepreneurship education? This research question was complemented by two additional research questions that were: How does teacher autonomy benefit the implementation of entrepreneurship education? and How do teachers want to utilize autonomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
10
1
1
Order By: Relevance
“…School management should pay attention to the fact that the teachers have the time, opportunities, and space to build an understanding of entrepreneurial competence together with other teachers. As noted in a previous research (Sommarström et al, 2021), teacher autonomy is important in understanding entrepreneurship education and, on the other hand, school management affects how a teacher is able to implement entrepreneurship education .…”
Section: Students' Self-assessment Toolmentioning
confidence: 88%
See 1 more Smart Citation
“…School management should pay attention to the fact that the teachers have the time, opportunities, and space to build an understanding of entrepreneurial competence together with other teachers. As noted in a previous research (Sommarström et al, 2021), teacher autonomy is important in understanding entrepreneurship education and, on the other hand, school management affects how a teacher is able to implement entrepreneurship education .…”
Section: Students' Self-assessment Toolmentioning
confidence: 88%
“…Earlier studies have confirmed that teachers implement entrepreneurial aspects in their teaching independently, but there are differences in the number and variation of entrepreneurship education methods used by teachers (Ruskovaara, 2014). Notwithstanding the large number and variation of materials, guiding documents and provided methods, in some cases teachers may have difficulties to implement entrepreneurial methods in their teaching (e.g., Sommarström et al 2021).…”
Section: Issues Controversies Problemsmentioning
confidence: 99%
“…Además, el programa permite cierta autonomía a los docentes para aplicar las diferentes actividades y seleccionar los recursos, lo que repercute positivamente en los resultados (Sommarström et al, 2021). En definitiva, el programa recoge 4 objetivos generales y 137 específicos, distribuidos por cada uno de los indicadores.…”
Section: Implementación De Un Programa De Formación Del Potencial Emp...unclassified
“…Therefore, China can carry out joint education in colleges and universities, and expand the number of exchange students. And students with entrepreneurial intentions should be encouraged to carry out entrepreneurship education from various angles (Sommarström et al, 2021).…”
Section: Analysis Of Entrepreneurship Education For Overseas Chinese Returnees Based On Psychological Resiliencementioning
confidence: 99%